“My Daughter is not like That”: A Qualitative Study of Parental Perception on Child Sexual Abuse Risk - S. Eelmaa (Дискурс)
Introduction. Parental prevention efforts on child sexual abuse (CSA) are paramount for children to have better protection. However, parental awareness and beliefs are essential constituents influencing parental prevention efforts. Previous studies have revealed that parents tend to judge child sexual abuse as a low risk to their children, which in turn impacts CSA prevention activities. The aim of this study was to explore parental beliefs on the risk of CSA, specifically victim- and perpetrator-specific risk of child sexual abuse to their children, as well as parents’ approaches to protecting their children.Methodology and sources. Data were collected from 22 parents during focus group interviews (n=6) combined with activity-oriented questions.Results and discussion. Based on data, four perpetrator and two victim-specific risk profiles were created. When parents find similarities between their children and perceived victims or perpetrators, it triggers the defensive othering effect, which acts as a subconscious protection mechanism, yet often creates inaccurate risk assessment and false confidence. The findings also tender that most parents do not teach their children the necessary skills related to CSA since they determine the risk to be low.Conclusion. This study adds to our understanding of CSA-related risk perception and prevention approaches, offering a conceptual addition to the defensive attribution theory. Further investigation is needed on the impacts of the cognitive processes and psychological protection mechanisms in relation to CSA risk assessment. The data from this study will be useful in developing CSA prevention programs and materials.